SPECIES COMPOSITION AND AN IDENTIFICATION KEY TO SPECIES OF THE TRIBE Coprini Kolbe, 1805 IN PU HOAT NATURE RESERVE - Van Bac, Bui; Van Sinh, Nguyen (Journal of Forestry Science and Technology, 2020)
Dung beetle species belong to three families: Scarabaeidae, Aphodiidae and Geotrupidae (Coleoptera: Scarabaeoidea), varying greatly in larval and adult ecologies. Dung beetles fulfill important functional roles in terrestrial ecosystems by burying and consuming animal dung and rotten fruits and fungi. This study investigates the species composition and community structure of dung beetles of the tribe Coprini Kolbe, 1805 (Scarabaeidae: Scarabaeinae) in the Pu Hoat Nature Reserve, an area belonging to the Western Nghe An Biosphere Reserve (Nghe An Province). So far, 35 species of the tribe Coprini have been recorded in Vietnam, most of them are large-bodied dung beetles. The trapping sites were deployed across a broad range of terrestrial habitats, being representative of the variety of agricultural and forestry environments present on the Pu Hoat Nature Reserve. Baited-pitfall traps and light traps were used to collect the Coprini dung beetles. In total, 12 Coprini species of three genera: Catharsius Hope, 1837, Synapsis Bates, 1868 and Copris Geoffroy, 1762 have been recorded for the first time in Pu Hoat Nature Reserve. In this study, we provide a thoroughly illustrated key to all recorded species of the tribe Coprini in Pu Hoat Nature Reserve. The key with a photographic guide would be broadly useful for both specialists and non-specialists in the identification of the Coprini species.